The practice of evaluation in innovation policy in Europe - Jakob Edler; Martin Berger; Michael Dinges; Abdullah Gök (The University of Manchester, Manchester Business School, 2011)
This paper characterises and analyses evaluation practice in national innovation policy across Europe. It is the first study that examines and interprets the characteristics, quality, usefulness, and consequences of evaluations in a systematic way. The analysis is based on the comprehensive INNO-Appraisal repository of 171 evaluation reports of national innovation policies of EU25 countries, conducted between 2002 and 2007. The paper seeks (1) to assess the state of the art of evaluation in innovation policy at national level, (2) to understand how different key dimensions of evaluation (timing, purpose, methods, tendering process, etc.) relate to each other, and (3) to explore types of evaluations. On that basis, we (4) draw lessons as to what constitutes good practice in evaluation, as the results of the survey have been exchanged and discussed with a number of policy makers of the sample responsible for the evaluation. The paper thus both contributes to the academic understanding of policy evaluation and supports use in policy practice.
Keywords: 330; Innovationspolitik; Bewertung; EU-Staaten